PERLINDUNGAN HUKUM BAGI PEKERJA BERDASARKAN PERJANJIAN KERJA WAKTU TERTENTU DALAM MASA PERPANJANGAN KONTRAK (STUDI KASUS PUTUSAN PENGADILAN NEGERI TANJUNG PINANG NOMOR 20/Pdt.Sus-PHI/2017/PN.Tpg) - Mikael Brian; Andari Yurikosari (Fakultas Hukum Universitas Tarumanagara, 2020)
The implementation of fixed-term employment agreements in Indonesia is commonplace. But there are some companies that use fixed-term employment agreements to look for profits. Many companies are not aware that seeking profit from monopolizing workers with a fixed-term employment agreement, instead becomes an act that rapes the rights of workers who work in the company itself. The economic and social aspects of workers are greatly influenced by these monopolistic acts. Termination of employment unilaterally and without clear reasons also often occur. Extension of fixed-term employment agreement should follow the existing legislation, especially Law Number 13 Year 2003 concerning Manpower. But as the author mentioned, many companies that apply for an extension of the fixed-term employment agreement deviate from the provisions of the law. Therefore, in this thesis the writer will analyze and conduct a more in-depth study of the extension of the work agreement that deviates from the provisions of the law and also what legal consequences will be obtained by the company and workers if that happens.